Malaysians' understanding of the nature of noncompliments from a gender perspective / Laily Yahya - Yahya, Laily (2005)
Being potentially interesting, the speech act of compliments has been extensively researched. in aspects such as compliment responses, gender differences and compliment categories. However, an aspect that is less explored in previous research is the nature of a non compliment among gender. As research in the area of a non-compliment has not yet been fully undertaken in Malaysia, therefore this study was carried out to investigate the perceptions of respondents and understanding of the nature of non-compliment from a gender perspective. It focused on reasons for a noncompliment: which gender has a greater tendency to refrain from giving compliments and the kind of impact that a noncompliment has on interactants. It also examined the relationship between a noncompliment and cultural background. Advocating the focus group as the methodology, the study highlighted the perceptions of the respondents (N =6) in an educational organization. The respondents in this study comprised of a homogenous group of (N): 3 Malay females and 3 Malay males. The data collected through the focus group discussions was transcribed and analyzed. The findings demonstrated how analyzing and interpreting noncompliments could generate interesting issues about gender differences. The data revealed that there were significant differences between the perceptions of men and women on the nature of noncompliments. Definitions of a compliment and a noncompliment are offered; the theoretical framework following Holmes (l988b) has been extended and refined. Additionally, a descriptive taxonomy has been outlined to best capture the essence of the nature of a noncompliment among the gender. The findings also imply that learners must be aware of the effects of non-compliments and how they violate the norms of politeness. Similarly, in teaching and teachers' development, an understanding of the powerful effect of non-compliments will enable teachers to gain insight into its discourse. Further research is recommended on other aspects which have not been sufficiently addressed in this study.